NADPH oxidase inhibitor apocynin decreases mitochondrial dysfunction and apoptosis in the ventral cochlear nucleus of D-galactose-induced aging model in rats. (March 2019) - Du, Zheng-De; Yu, Shukui; Qi, Yue; Qu, Teng-Fei; He, Lu; Wei, Wei; Liu, Ke; Gong, Shu-Sheng
Abstract: Presbycusis has become a common sensory deficit in humans. Oxidative damage to mitochondrial DNA and mitochondrial dysfunction is strongly associated with the aging of the auditory system. A previous study established a mimetic rat model of aging using D-galactose (D-gal) and first reported that NADPH oxidase-dependent mitochondrial oxidative damage and apoptosis in the ventral cochlear nucleus (VCN) might contribute to D-gal-induced central presbycusis. In this study, we investigated the effects of apocynin, an NADPH oxidase inhibitor, on mitochondrial dysfunction and mitochondria-dependent apoptosis in the VCN of D-gal-induced aging model in rats. Our data showed that apocynin decreased NADPH oxidase activity, H2 O2 levels, mitochondrial DNA common deletion, and 8-hydroxy-2-deoxyguanosine (8-OHdG) expression and increased total superoxide dismutase (T-SOD) and glutathione peroxidase (GSH-Px) activity in the VCN of D-gal-induced aging model in rats. Moreover, apocynin also decreased the protein levels of phospho-p47 phox (p-p47 phox ), tumor necrosis factor alpha (TNFα), and uncoupling protein 2 (UCP2) in the VCN of D-gal-induced aging model in rats. Meanwhile, apocynin alleviated mitochondrial ultrastructure damage and enhanced ATP production and mitochondrial membrane potential (MMP) levels in the VCN of D-gal-induced aging model in rats. Furthermore, apocynin inhibited cytochrome c (Cyt c) translocation from mitochondria to the cytoplasm and suppressed caspase 3-dependent apoptosis in the VCN of D-gal-induced aging model in rats. Consequently, our findings suggest that neuronal survival promoted by an NADPH oxidase inhibitor is a potentially effective method to enhance the resistance of neurons to central presbycusis. Highlights: D-galactose injection mimics the biologic aging process in the VCN of rats. NADPH oxidase-associated ROS is responsible for mitochondrial dysfunction and apoptosis in the VCN of aging rats. NADPH oxidase inhibitor apocynin alleviates mitochondrial oxidative damage in the VCN of aging rats. NADPH oxidase inhibitor apocynin improves mitochondrial function in the VCN of aging rats. NADPH oxidase inhibitor apocynin decreases mitochondria-dependent apoptosis in the VCN of aging rats.